Stubble mulching and minimum tillage with barley (1993)
In the Colombian Tibaitatá CNI (2500 m.a.s.l., 14°C an bimodal rainfall) was carried out a soil management as an alternative for minimizing environmental constraints for barley or wheat production in a medial isomesic Dystric Haplustand, Some progress has been obtained by adoption of minimum tillage with or without straw in the arable layer, to minimize the negative effects of both low and bad distributed rainfall during the cropping season. By reducing soil disturbance, grain yield was better and had an increase in water content in the surface arable layer, associated with an improving penetrability. Other units using cereal straw (4 and 8 t/ha)and minimum tillage only improve physical soil  properties.